Physiological, biochemical, anthropometric, and biomechanical influences on exercise economy in humans. (27th March 2017) - Lundby, C.; Montero, D.; Gehrig, S.; Andersson Hall, U.; Kaiser, P.; Boushel, R.; Meinild Lundby, A.‐K.; Kirk, N.; Valdivieso, P.; Flück, M.; Secher, N. H.; Edin, F.; et al.
Abstract : Interindividual variation in running and cycling exercise economy (EE) remains unexplained although studied for more than a century. This study is the first to comprehensively evaluate the importance of biochemical, structural, physiological, anthropometric, and biomechanical influences on running and cycling EE within a single study. In 22 healthy males (VO2 max range 45.5‐72.1 mL·min −1 ·kg −1 ), no factor related to skeletal muscle structure (% slow‐twitch fiber content, number of capillaries per fiber), mitochondrial properties (volume density, oxidative capacity, or mitochondrial efficiency), or protein content (UCP3 and MFN2 expression) explained variation in cycling and running EE among subjects. In contrast, biomechanical variables related to vertical displacement correlated well with running EE, but were not significant when taking body weight into account. Thus, running EE and body weight were correlated ( R 2 =.94; P <.001), but was lower for cycling EE ( R 2 =.23; P <.023). To separate biomechanical determinants of running EE, we contrasted individual running and cycling EE considering that during cycle ergometer exercise, the biomechanical influence on EE would be small because of the fixed movement pattern. Differences in cycling and running exercise protocols, for example, related to biomechanics, play however only a secondary role in determining EE. There was no evidence for an impact of structural or functional skeletal muscle variables on EE. Body weight was the main determinant of EE explaining 94% of variance in running EE, although more than 50% of the variability of cycling EE remains unexplained.